Abrupt shifts of productivity and sea ice regimes at the western Barents Sea slope from the Last Glacial Maximum to the Bølling-Allerød interstadial. (15th October 2019) - Köseoğlu, Denizcan; Belt, Simon T.; Knies, Jochen
Abstract: Advanced knowledge of spatio-temporal constraints on the Barents Sea Ice Sheet during the late Weichselian glaciation overshadows relatively limited understanding of seasonal sea ice (experiencing an annual advance-retreat cycle) and primary productivity trends accompanying massive, abrupt climate changes during glacial-deglacial cycles. Such paleo-reconstructions are crucial prerequisites for improved comprehension and prediction of current and future climate change. Here, we investigate sea ice and phytoplankton biomarker distributions in a Barents Sea sediment core covering ca. 25.8–15.4 cal kyr BP to elucidate abrupt shifts of spring–summer sea ice concentrations and relative sympagic–pelagic productivity trends at the southwestern continental slope. Despite significant presence of seasonal sea ice, the Last Glacial Maximum (LGM) and initial shelf edge deglaciation (SEDG) at the core site are characterised by occurrence of productive coastal polynya adjacent to the maximum ice sheet extent. The onset of perennial (i.e. multi-year) ice cover and near-zero productivity during Heinrich Stadial 1 (HS1; ca. 18.0–16.3 cal kyr BP) accompanies significant meltwater fluxes from ice sheet debuttressing and the consequent stagnation of thermohaline circulation. Rapid sea ice retreat and unprecedented pelagic productivity observed after 16.3 cal kyr BP coincides with areal ice sheet deglaciation and is potentially linked to the release of sub-surface heat and nutrient reservoirs, together with reinvigorated deep water circulation following millennial heating of the deep ocean during HS1. We find that a multivariate fingerprinting approach involving assessment of both downcore and surface biomarker distributions is able to distinguish relative ice-algal and pelagic diatom productivity driven by sea ice dynamics. Highlights: Seasonal sea ice and high sympagic productivity characterised the LGM. Abrupt decline of productivity coincided with perennial ice cover during the HS1. Unprecedented pelagic productivity dominated following the post-HS1 ice retreat. Multivariate HBI biomarker set can decouple sympagic and pelagic productivity.